Hepatic transcriptomic response in aequidens metae to Polycyclic Aromatic Hydrocarbons (PAH) (2021)
Aquatic systems receive Polycyclic aromatic hydrocarbons (PAH) through atmospheric deposition and direct runoff release, being fish one of the targets with a particular interest because they occupy key positions in aquatic and terrestrial food webs. In fact, exposure to different PAH can generate specific responses in gene expression profiles associated with biotransformation that could be used as biomarkers of exposure to these hydrocarbons. In this regard, RNA sequencing (RNA-seq) has provided insight into response mechanisms in gene expression studies by integrating data on biological effects in response to sublethal PAH exposure in non-model organisms without available genomic information. However, there are no transcriptomic profiling studies in fish in Colombia. Therefore, the objective of the present study was to characterize the hepatic transcriptional response in the non-model fish Aequidens metae exposed to polycyclic aromatic hydrocarbons under acute exposure.Liver samples were taken from adult specimens exposed via intraperitoneal to six conditions with five replicates, no injection control, solvent vehicle control, ßnaphthoflavone (BNF), naphthalene (NAP), phenanthrene (PHE) and benzo[a]pyrene (BaP), transcriptomic analysis of RNA-seq derived data was performed. A total of 396 differentially expressed genes (DEG) were identified for the comparison between solvent and BNF, 330 for NAP, 396 for PHE and 381 for BaP of which 15 genes were common to all 4 PAH. In turn, enrichment analysis identified 9, 31, 12 and 31 KEGG pathways for BNF, NAP, PHE and BaP, respectively. In general, the pathways affected were associated with the processes of cell growth and death; lipid and carbohydrate metabolism; transport and catabolism; folding, sorting and degradation; the endocrine system; signal transduction; xenobiotic metabolism; nucleotide metabolism; viral infectious diseases and the endocrine system. Overall, the analysis showed evidence of toxic effects on liver tissue in fish exposed to the different PAH underlying molecular mechanisms through the study of transcriptomic profiling being a pioneer study in Colombian fish in this area. Acknowledgment: This study was funded by Colciencias-ANH and Universidad de los Llanos project No 162-2016 and also a Project from the Pontificia Universidad Javeriana from Colombia.